An Integrated Review Of “Sarvasara Mukharoga” Or “Mukhapaka” W.S.R. To Oral Submucous Fibrosis (OSF) - Mehar, Kapil; Chowdhury, Nur Mohammad Iqbal; Vardhan, Prabhakar; Joshi, Ram Kishor (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda explains this feature of mouth ulcer as a characteristic feature of paittik individuals. In excess consumption of extremely pungent and spicy food. It may also occur for the reason that of chewing of chemical agents like tobacco, insomnia and vitamin insufficiency, much life threatening disease like malignancy, submucosal fibrosis, skin disease and disturbances in gastro intestinal tract like constipation.